2017
DOI: 10.1016/j.sna.2017.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ZnO nanorods by microwave-assisted chemical-bath deposition for highly sensitive self-powered UV detection application

Abstract: High-quality vertically aligned zinc oxide (ZnO) nanorods were successfully grown on seeded silicon substrates p-Si(100) through microwave-assisted chemical bath deposition. Structural and morphological analyses revealed hexagonal wurtzite nanorods perpendicular to the substrate along the c-axis in the direction of the (002) plane. Optical measurements showed a high-intensity UV peak with a low broad visible peak. UV emission was compared with the visible emission having an IUV/Ivis ratio of 53. A metal-semico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…For the responsivity performance, the stability Schottky barriers height play an important role. 43 Also, the existence of strong depletion width could make influence in the responsivity improvement. It can be observed that the maximum responsivity of the device is 300 mA W −1 at 4.5 V applied bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the responsivity performance, the stability Schottky barriers height play an important role. 43 Also, the existence of strong depletion width could make influence in the responsivity improvement. It can be observed that the maximum responsivity of the device is 300 mA W −1 at 4.5 V applied bias.…”
Section: Resultsmentioning
confidence: 99%
“…This value of responsivity is larger than the value reported by Pei 44 and as comparable to ZnO PDs reported by other groups. 43,45 P. S. Shewale et al 46 reported the highest value of responsivity for Ti doped ZnO PDs about 50 mA W À1 . Our photocurrent measurements allowed us to determine the quantum efficiency that corresponds to the number of electron-hole pairs generated by incident photon, it expressed by:…”
Section: I-v-t Characteristics Of the Ni Doped Zno Nps Uv Photodetectormentioning
confidence: 99%
“…One interesting method is the hydrothermal synthesis under microwave radiation since it is a low-cost, low-temperature, and fast method, yet allowing a high yield production of hexagonal wurtzite structures [46,64]. Despite the advantages, ZnO NRs produced through this method have been essentially explored for UV sensors [46,51,65,66], gas sensors [67][68][69][70], and photocatalysis [49,71,72], yet not for NGs.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, ZnO, as an important II-VI semiconductor with a direct band gap of 3.37 eV, larger exciton binding energy of 60 mV [9,10] at room temperature, and piezoelectricity [11], has attracted special interest. Especially, vertically aligned ZnO nanorod arrays (ZNAs), due to their non-toxicity, low-cost, large surface to volume ratio, and ease of large scale fabrication, can be employed in many devices, like solar cells, UV lasers, gas sensors, UV detectors, and photocatalysis [12][13][14][15][16][17][18][19][20]. Various methods have been used to synthesize ZNAs, including chemical vapor deposition (CVD) [21,22], pulsed laser deposition (PLD) [23], molecular beam epitaxy (MBE) [10,24], etc.…”
Section: Introductionmentioning
confidence: 99%